2016
DOI: 10.1080/09168451.2016.1210499
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of the L-lysine metabolites, L-2-aminoadipic acid and L-pipecolic acid, on protein turnover in C2C12 myotubes

Abstract: We previously showed that L-lysine (Lys) and a metabolite of Lys, L-saccharopine, suppressed autophagic proteolysis in C2C12 myotubes. However, the effects of other metabolites of Lys on protein turnover were unknown. We here investigated the effect of the Lys metabolites, L-2-aminoadipic acid (2-AA) and L-pipecolic acid (Pip), on protein turnover in C2C12 myotubes. 2-AA suppressed myofibrillar protein degradation evaluated by the 3-methylhistidine and autophagy activity evaluated by light chain 3-II at lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Supplementation of lysine in rats could reduce the upregulated autophagy activity of skeletal muscle caused by a low-protein diet and activate the Akt/mTOR signaling pathways [ 24 ]. As a metabolite of lysine, pipecolic acid also could stimulate the rates of protein synthesis, contributing to the effect of lysine on protein turn over in skeletal muscle [ 25 ]. We found that serum pipecolic acid was positively associated with muscle mass and muscle strength, but negatively associated with age.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of lysine in rats could reduce the upregulated autophagy activity of skeletal muscle caused by a low-protein diet and activate the Akt/mTOR signaling pathways [ 24 ]. As a metabolite of lysine, pipecolic acid also could stimulate the rates of protein synthesis, contributing to the effect of lysine on protein turn over in skeletal muscle [ 25 ]. We found that serum pipecolic acid was positively associated with muscle mass and muscle strength, but negatively associated with age.…”
Section: Discussionmentioning
confidence: 99%
“…α-Aminoadipic acid is a lysine metabolite which decreases fasting glucose concentrations and enhances insulin sensitivity in animals in vivo ( 71 , 72 ). α-Aminoadipic acid suppresses protein degradation and autophagy in vitro, with concomitant upregulation of the Akt/mTOR signaling pathway ( 73 ). This evidence is of interest given the elevation of this metabolite in protein-fed conditions compared with the fasted state, potentially suggesting a mitigation of protein degradation in these nutritional groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally well tolerated, and skin-related complaints, nausea, and dizziness are the most common patient-reported side effects [40]. LAA, a selective astrocytic toxin, has been demonstrated to exert some regulatory effects on tibia fracture [41], myotubes [42], and retina [43], thus contributing to the fracture-induced nociceptive, cell autophagy in myotubes, and retinal vascular responses. It has not yet been clinically applied due to its unusual astroglial toxin, which may trigger locomotor network damage.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%